2008
DOI: 10.1186/1471-2164-9-391
|View full text |Cite
|
Sign up to set email alerts
|

Partial duplication of the PRLR and SPEF2 genes at the late feathering locus in chicken

Abstract: Background: One of the loci responsible for feather development in chickens is K. The K allele is partially dominant to the k+ allele and causes a retard in the emergence of flight feathers at hatch. The K locus is sex linked and located on the Z chromosome. Therefore, the locus can be utilized to produce phenotypes that identify the sexes of chicks at hatch. Previous studies on the organization of the K allele concluded the integration of endogenous retrovirus 21 (ev21) into one of two large homologous segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
107
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 27 publications
6
107
0
6
Order By: Relevance
“…Strikingly, in addition to a PRLR gene localized on chromosome Z, a partially duplicated PRLR gene (designated as dPRLR gene herein) has also been identified recently (Elferink et al 2008). The dPRLR gene was found within the sex-linked late-feathering (LF) K locus on chromosome Z, within which a partial duplication of sperm flagellar 2 gene (named dSPEF2) was identified simultaneously (Elferink et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, in addition to a PRLR gene localized on chromosome Z, a partially duplicated PRLR gene (designated as dPRLR gene herein) has also been identified recently (Elferink et al 2008). The dPRLR gene was found within the sex-linked late-feathering (LF) K locus on chromosome Z, within which a partial duplication of sperm flagellar 2 gene (named dSPEF2) was identified simultaneously (Elferink et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The dPRLR gene was found within the sex-linked late-feathering (LF) K locus on chromosome Z, within which a partial duplication of sperm flagellar 2 gene (named dSPEF2) was identified simultaneously (Elferink et al 2008). It has been reported that this dominant sex-linked K allele is associated with the LF phenotype of newly hatched chicks with the retarded emergence of flight feathers, while the recessive kC allele determines the early-feathering (EF) phenotype of chicks (Serebrovsky 1922, Elferink et al 2008. The identification of the dPRLR gene within the K locus (but not within the kC locus) suggests that dPRLR is probably a candidate gene associated with LF development in chicks (Elferink et al 2008, Wang et al 2010a, Luo et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…이들 중 우모 발생 속도에 관여하는 만우성 유 전자를 이용한 깃털 감별법(feather-sexing)이 산업적으로 가 장 널리 이용되고 있다 (Mueller and Moultrie, 1952;Plumart and Mueller, 1954;Siegel et al, 1957;Somes, 1969;Warren, 1976;McGibbon, 1977;SAFRS, 2011, Sohn et al, 2012. 깃 털 감별법은 우모 발생 속도에 관여하는 조우성(early-fea- et al, 1988;Iraqi and Smith, 1995;Bitgood, 1999;Elferink et al, 2008) (Plumart and Mueller, 1954;Somes, 1970;Dunnington and Siegel, 1986a), 일부 연구자들은 성장율과 이들 형 질간에 거의 관련이 없다고 하였다 (Hays, 1951;Godfrey and Farnsworth, 1952;Lowe et al, 1965). 또한 조우성 개체들의 산란능력 및 난중이 만우성 개체에 비해 우수하고, 초산 일 령도 빠르다고 하였으나 (Lowe et al, 1965;Harris et al, 1984), 조만성이 산란능력에 큰 영향이 없음도 보고하고 있 다 (Lowe and Garwood, 1981).…”
unclassified
“…생존율과 깃털 조만성 간에는 밀접한 관련이 있음을 보고하고 있는데 만우성 유전 자가 ev21 유전자와 매우 가깝게 연관되어 있어 lymphoid leucosis virus에 대한 감염율을 증가시키고 따라서 폐사율을 증가 시키는 것으로 밝혀졌다 (Harris et al, 1984;Bacon et al, 1988;Fadly, 1988, 1994;Iraqi and Smith, 1995). 이와 더 불어 조만성 유전자 좌위에 대한 연구도 활발히 진행되어 조우성 유전자와 만우성 유전자의 분자유전학적 식별 방법을 개발하고 (Smith and Levin, 1991;Tixier-Boichard et al, 1994 Iraqi andSmith, 1995), 나아가 만우성 개체의 homozygous와 heterozygous의 구분도 가능함을 제시하였다 (Elferink et al, 2008 …”
unclassified
“…, 1977, SAFRS, 2011. 이러한 깃털감별법(feathersexing)은 조우성(rapid-feathering)과 만우성(slow-feathering)에 관여하는 유전자(K, k + )가 Z 염색체에 위치하기 때문에 (Bacon et al, 1988;Lakshmanan et al, 1992;Iraqi and Smith, 1995;Bitgood, 1999Elferink et al, 2008 (Spillman, 1908;Punnett, 1923;Nickerson, 1944;Bitgood, 1988;Campo, 1991;Kerje et al, 2003;Dorshorst and Ashwell, 2009;Hellstrom et al, 2010), 왜소유전자 (Hutt, 1959;Bernier and Arscott, 1960;Cole and Austic, 1980;Stewart et al, 1984;BurghelleMayeur et al, 1989;Tixier-Boichard et al, 1990;Merat et al, 1994;Vasilatos-Younken et al, 1997;Cole, 2000), 색소침 착억제유전자 (Bitgood, 1985(Bitgood, , 1988Levin et al, 1993;Zhang et al, 2000;Dorshorst and Ashwell, 2009), 만우성유전자 (Somes, 1969(Somes, , 1975Harris et al, 1984;Bacon et al, 1986Bacon et al, , 1988Smith and Nelsen, 1993;Bitgood, 1999;Fotsa et al, 2001;Hamoen et al, 2001;Khosravinia, 2009), 안구돌출유전 자 (Bitgood and Whitley, 1986;…”
mentioning
confidence: 99%